The Analysis Study of Home - Based Rehabilitation Program for Stroke Patients: A Comprehensive Systematic Review - Azzren Virgita Pasya; Risa Margaretta; Zahrina Amalia Eka Nurfadillah (International Medical Journal Corp. Ltd, 2025)
Background: Home-based rehabilitation offers a convenient and effective alternative for stroke patients, utilizing telerehabilitation and virtual reality therapy. These therapeutic interventions have shown promising results in improving motor function and daily living activities. However, integrating these programs into standard stroke care requires a comprehensive understanding of their efficacy, safety, and implementation challenges. Methods: This systematic review followed PRISMA 2020 guidelines and concentrated solely on full-text articles published in English from 2015 to 2025. Editorials and review articles lacking a DOI were excluded to maintain the integrity of high-quality sources. A literature review was performed using reputable databases such as ScienceDirect, PubMed, and SagePub to identify pertinent studies. Result: The initial database search produced more than 600 pertinent publications on the subject. After a thorough three-stage screening process, eight studies fulfilled the established inclusion criteria and were chosen for detailed analysis. Each study underwent a detailed critical evaluation, facilitating an in-depth analysis of the Home-Based Rehabilitation Program for Stroke Patients. This systematic approach ensured that the analysis was based on high-quality evidence, aligned with the study's objectives, and capable of yielding significant insights into this complex association. Conclusion: Stroke rehabilitation programs, incorporating telerehabilitation and virtual reality (VR), offer a viable alternative to traditional settings. These technologies improve functional outcomes, but addressing implementation challenges and ensuring equitable access is crucial for maximizing benefits. Future research should focus on user-centered designs and long-term outcomes.